2020
DOI: 10.3390/foods9121876
|View full text |Cite
|
Sign up to set email alerts
|

Blending Emotions and Cross-Modality in Sonic Seasoning: Towards Greater Applicability in the Design of Multisensory Food Experiences

Abstract: Sonic seasoning refers to the way in which music can influence multisensory tasting experiences. To date, the majority of the research on sonic seasoning has been conducted in Europe or the USA, typically in a within-participants experimental context. In the present study, we assessed the applicability of sonic seasoning in a large-scale between-participants setting in Asia. A sample of 1611 participants tasted one sample of chocolate while listening to a song that evoked a specific combination of cross-modal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Cross-sensory response research in [ 29 ], specifically studies in the human taste response to music, has pioneered Bayesian alternatives to frequentist analysis of Likert-scaled data. In [ 29 ] a sample of 1611 participants tasted one sample of chocolate while listening to a song that evoked a specific combination of cross-modal and emotional consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sensory response research in [ 29 ], specifically studies in the human taste response to music, has pioneered Bayesian alternatives to frequentist analysis of Likert-scaled data. In [ 29 ] a sample of 1611 participants tasted one sample of chocolate while listening to a song that evoked a specific combination of cross-modal and emotional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sensory response research in [ 29 ], specifically studies in the human taste response to music, has pioneered Bayesian alternatives to frequentist analysis of Likert-scaled data. In [ 29 ] a sample of 1611 participants tasted one sample of chocolate while listening to a song that evoked a specific combination of cross-modal and emotional consequences. The researchers addressed difficulties in interpreting frequentist statistical tests using discrete, categorical responses by applying a Bayesian model to quantify the information content of a response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedonic/emotional sensation transference effects from music to taste have also been demonstrated (e.g., Reinoso-Carvalho et al, 2019, 2020a. Indeed, some of the most exciting recent research has shown that sonic seasoning and sonic sensation transference can be combined and thus be triggered concurrently (see Reinoso-Carvalho et al, 2020b). In the latter study, for instance, Reinoso-Carvalho et al chose one pair of musical tracks designed to induce emotion, and another pair of tracks that had been demonstrated to give rise to sonic seasoning.…”
Section: Sonic Sensation Transference: Musical Affect/emotionmentioning
confidence: 99%
“…The downside of using specially composed music tracks (or soundscapes) is that they may not offer the same emotional punch as more recognizable popular music tracks (e.g., Reinoso-Carvalho et al, 2020a , b ). This is important, given that the latest research from Reinoso-Carvalho and his colleagues suggesting that “sensation transference” effects may be more pronounced than sonic seasoning (see also ‘The delicate connection between sound and taste’, 2021 ).…”
Section: Multisensory Flavour Perception and Sonic Seasoning: The Basicsmentioning
confidence: 99%